The metallurgical characteristics of non-precious alloys using Nd:YAG laser welding - Lee, Jun-Hee (Biomater Res, 2015)
BACKGROUND: This study aimed to determine the effect of hardness change according to penetration depth in the laser fusing zone and observed the correlation of the microstructure as an Nd:YAG laser was irradiated to Ni-Cr alloy for dental use by setting the spot diameter size with respect to defocusing distances. In all groups, the hardness depth profiles in the laser fusing zone and heat-affecteded zone (HAZ) had larger values than those of the base metal. In addition, the hardness values in places beyond the fusing zone and the HAZ were measured as being quantitatively lower. METHODS: The alloys used in this study were Verabond 2 V, Noritake Super, and Bellabond Plus, which are commercially used non-precious dental alloys. The specimens were cut to have a plate shape with a size of 0.5 × 3.0 × 2.5 mm. This was followed by setting the Nd:YAG laser output, pulse duration, and frequency to 60 W, 10 ms, and 5 Hz, respectively. The laser was then irradiated as the spot diameter condition varied between 0.5 mm and 1.4 mm in accordance with defocusing distance from 0.0 mm to 2.0 mm. After the laser irradiation, a cross-section of the fusing zone in the specimens was observed in terms of laser melted depth, hardness depth profile, and the microstructure of each alloy. RESULTS: The observation result of the diffusion of the constituent elements and microstructure using field emission scanning electron microscopy, energy dispersive spectroscopy (EDS), and electron probe micro-analyzer showed that the fusing zone revealed a much finer dendritic form than the base metal due to the self-quenching effect after laser melting, while no change in constituent elements was found although some evaporation of the main elements was observed. CONCLUSIONS: These results suggest that each Mo and Si combined inter-metallic compounds were formed on the interdendritic area. Through this study, the laser fusing zone had better hardenability due to the inter-metallic compound and grain refinement effect.